Unlawful Acts and Legal Bullying: A Normative-Empirical Juridical Analysis of Case No. 1206/PDT.G/2025/PN JKT.BRT - I Nyoman Suandika; Hanphie Agusoeito (Riviera Publishing, 2026)
This research analyzes two issues: first, the harmonization of norms between the provisions of unlawful acts (PMH) Article 1365 of the Civil Code and the instrument for the protection of the right to information in determining the limits of legitimate educational expression; second, the qualification of a lawsuit based on Article 1365 of the Civil Code against financial educators on social media as onrechtmatige procesvoering/misbruik van recht. The research uses normative-empirical juridical methods with legislative, conceptual, case, and comparative approaches, focusing on Case Number 1206/Pdt.G/2025/PN Jkt.Brt, PT. Tunas Tangkas Primaraga Sakti against financial educator Apriliana. The results of the study show that Article 1365 of the Civil Code does not provide an operational definition of the element of